Microbial Changes and Host Response in F344 Rat Colon Depending on Sex and Age Following a High-Fat Diet - Lee, Sun Min; Kim, Nayoung; Yoon, Hyuk; Nam, Ryoung Hee; Lee, Dong Ho (Frontiers in Microbiology, 2018)
Gut microbiota, an important component that affects host health, change rapidly and directly in response to altered diet composition. Recently, the role of diet-microbiome interaction on the development of colon cancer has been the focus of interest. Colon cancer occurs more frequently in an aged population, and in males. However, the effect of dietary changes on the gut microbiome has been studied mainly in young males, even though it may vary with age and sex. The aim of this study was to investigate microbial changes and host response in the colons of male and female 6-week-old (young) and 2-year-old (old) Fisher-344 rats exposed to a high-fat diet (HFD). Our results showed that exposure to HFD for 8 weeks decreased the species richness of microbiota (Chao1) and increased Firmicutes/Bacteroidetes ratio only in aged rats, and not in young rats. Sex differences underlying the alteration by HFD in the gut microbiome were observed in the microbiome of aged rats. For instance, the abundance ratio of Akkermansia muciniphila and Desulfovibrio spp. increased in response to HFD in young rats and female aged rats, but not in male aged rats. Histological inflammation and cell proliferation of colon mucosa (indexed by Ki67) were significantly increased by HFD even in young rats; aged rats showed significantly higher cell proliferation in the HFD group than in the control. The HFD-induced decrease of species richness and the increase in specific species (Desulfovibrio spp. and Clostridium lavalense), which produce carcinogenic compounds such as H2S and N-nitroso compounds, were significantly correlated with Ki67 index. In colon mucosa, the concentration of myeloperoxidase was increased by HFD only in males, and not in females. In conclusion, the results suggest a link between HFD-induced gut dysbiosis (particularly the low species richness and high abundance ratios of Desulfovibrio spp. and C. lavalense) and cell proliferation of colon mucosa (indicated by Ki67 IHC). In addition, sex differences influence the response of gut microbiome to HFD particularly in old age. Such sex differences in the gut microbiota might be related to sex differences in inflammation in the colon mucosa.